Site, local, and regional earthquake ground motion characterization and application. Issue 1 (January 2017) - Hong, HP; Liu, TJ
A systematic overview and comparison is presented on the seismic hazard assessment based on the observations and seismic hazard model and the characteristics of earthquake ground motions for a site, a local area, and a region. It shows that the seismic hazard estimated by directly using the observations could differ from that evaluated using an adopted seismic hazard model. It indicates the importance to judiciously select the seismic hazard model, as well as to understand that historical records for a limited period may not fully reflect the seismic hazard. The comparison of the ground motion characteristics is focused on the variability of the ground motion measures, the coherency for record components in two orthogonal orientations, and the spatial correlation and spatial coherency. Procedures for simulating bidirectional excitations at a site and record components at multiple sites for a scenario seismic event are given. The application of the simulated record components to estimate the seismic loss for a portfolio of hypothetical buildings by considering a scenario event is shown, indicating the effectiveness of the presented methodology for seismic loss estimation.